Prevalence and factors associated with neonatal mortality at the neonatal intensive care unit at St. Mary’s Hospital Lacor, Northern Uganda - Nicholas Aguma; Steven Ekak; Lambert Emetu; Samson Ojok; Peter Akera (BMC Pediatrics)
Abstract Background Worldwide, neonatal mortality is a major public health burden especially in the developing countries. Several factors are associated with neonatal mortality at the neonatal intensive care unit (NICU). The aim of this study was to determine the prevalence and factors associated with neonatal mortality among neonates admitted to the NICU at St. Mary’s Hospital Lacor in Northern Uganda. Method The study collected quantitative data through retrospective descriptive review of records of 423 systematically sampled neonates admitted to the NICU between January 1st 2023 and December 31st 2023. Socio demographics, pregnancy related and neonatal variables of mothers and the neonates admitted to the NICU were entered in a pre-tested data abstraction tool adapted and modified from a similar study. Neonatal mortality was described as a proportion of the total number of neonates who were admitted. Logistic regression analyses using odds ratios with 95% confidence interval (CI) were used to assess the association between possible factors associated with neonatal mortality. An adjusted odds ratio (aOR), namely an odds ratio (OR) that has been adjusted to account for other predictor variables, is provided. Data was analysed using SPSS 27.0 statistical software (SPSS, Inc., Chicago, IL, USA). Results There were 74 (17.49%) neonatal deaths. 70.27% of the neonatal deaths were early neonatal deaths. Preterm deaths contributed over 81.10% to the overall mortality. Preterm birth (aOR = 3.81, 95% CI 1.14 − 12.78), low APGAR at 5 min (aOR = 4.52, 95% CI 2.04 − 10.01), and late initiation of breastfeeding (OR = 2.79, 95% CI 1.50 − 5.18) were significant factors associated with neonatal death. Conclusion The neonatal mortality rate in NICU observed in this study was high. The majority of the deaths occurred in the early neonatal period. More than 80% of deaths recorded were due to prematurity. Preterm birth, low birth weight, low 5th minute APGAR score and late initiation of breastfeeding were significant risk factors for neonatal death. Efforts to address preterm birth, quality neonatal resuscitation and early initiation of breastfeeding are critical to achieving survival goals in newborns.